GRAVITY'S PULL - MariNaomi (Minneapolis : Graphic Universe, 2019)
Claudia Jones has returned to Blithedale High School, but rumors about her possible alien abduction persist as everyone begins to feel the strange effects of her presence.
Ages 14 and up.
Keywords: Graphic novels. -- Fiction; Alien abduction -- Fiction; Missing children -- Fiction; High schools -- Fiction; Schools -- Fiction; Graphic novels